Sport marketing - Dees, Windy PhD 1977-; Mullin, Bernard James PhD; Hardy, Stephen 1948- PhD; McEvoy, Chad D. EdD 1971-; McKelvey, Stephen 1959- JD; Sutton, William Anthony 1951- EdD; Walsh, Patrick PhD 1978- (Champaign, IL Human Kinetics, Inc., 2022)
This book helps students prepare for careers in the fast-paced world of sport marketing, as well as provides a resource for practitioners looking for the latest information in the field. The book offers abundant examples of the latest issues in the competitive marketplace
Chapter 1. The special nature of sport marketing -- Chapter 2. Strategic marketing management -- Chapter 3. Understanding the sport consumer -- Chapter 4. Market research and analytics in the sport industry -- Chapter 5. Market segmentation and target marketing -- Chapter 6. The sport product -- Chapter 7. Managing sport brands -- Chapter 8. Promotion and paid media -- Chapter 9. Public relations -- Chapter 10. Sponsorship, corporate partnerships, and the role of activation -- Chapter 11. Social media in sports -- Chapter 12. Sales and service -- Chapter 13. Delivering and distributing core products and extensions -- Chapter 14. Legal aspects of sport marketing -- Chapter 15. The evolving nature of sport marketing
Includes bibliographical references and index
Keywords: Sports -- Marketing